Isolated Central Nervous System Presentation of Early T-Cell Precursor Acute Lymphoblastic Leukemia/Lymphoma: A Rare Case of Exclusive Brain Involvement - Violet O. Swart; Behyar Zoghi (Case Reports in Hematology)
Early T-cell precursor acute lymphoblastic leukemia/lymphoma (ETP-ALL/LBL) is a high-risk and biologically distinct subset of T-cell acute lymphoblastic leukemia, typically characterized by leukemic involvement of bone marrow, peripheral blood, and mediastinal structures. Central nervous system (CNS) involvement is typically a secondary manifestation [1, 2, 3]. We report a rare case of isolated CNS presentation of ETP-ALL/LBL in a 73-year-old woman who presented with progressive neurological symptoms. Imaging revealed a large right frontal extra-axial mass. Systemic evaluation, including peripheral blood flow cytometry and CT imaging of chest, abdomen, and pelvis, showed no evidence ofsystemic disease. Surgical resection and subsequent histopathology confirmed the diagnosis of ETP-ALL/LBL. A bone marrow biopsy was deffered to the patient’s preference and rapid clinical deterioration. This case underscores the diagnostic and therapeutic challenges of CNS-restricted leukemic presentations and highlights the need for early recognition and CNS-directed diagnostic evaluation.